Comparison of levels of von Willebrand factor and ADAMTS13 in Patients of Myocardial Infarction and Healthy Controls - Shamila Tahir,Nazish Mazari,Aisha Chauhdry,Ghulam Mustafa, Shabbir Hussain,Faheem Shahzad, Shahida Mohsin, Shamila Tahir,Nazish Mazari,Aisha Chauhdry,Ghulam Mustafa, Shabbir Hussain,Faheem Shahzad, Shahida Mohsin (Journal of Rawalpindi Medical College, 2019)
Background: to determine the levels of von Willebrand factor (vWF) and ADAMTS13 in patients of myocardial infarction and healthy controls Methods: In a comparative study, the samples were collected from 45 myocardial infarction patients and 45 age and sex matched healthy controls. Total 5ml blood was collected in tri-sodium citrated vials. The determination of VWF was carried out by chromogenic assay on Stago and ADAMTS13 assay was carried out by standard ELISA kit. The Mann Whitney U test was used to determine the median difference between two groups (patients and control). Results; Patients with MI had higher median plasma level of VWF (161%) as compared to healthy controls (120%). The median plasma level of ADAMTS13 of control and patients was 56.54 U/L and 18.80 U/L respectively. The difference in median plasma levels of VWF & ADAMTS13 between groups was statistically significant (p < 0.001 Conclusion: Plasma VWF and ADAMTS13 had a significant association with MI patients. There exists an inverse correlation between plasma VWF and ADAMTS13 levels in MI patients, but this correlation was very weak in control group.